Clinical usefulness of instantaneous wave-free ratio for the evaluation of coronary artery lesion with prior myocardial infarction: A multi-center study. (February 2020) - Fukuoka, Shusuke; Kurita, Tairo; Takasaki, Akihiro; Nakata, Tomoyuki; Fujimoto, Naoki; Masuda, Jun; Hoshino, Kozo; Tanigawa, Takashi; Koyabu, Sukenari; Ito, Masaaki; Dohi, Kaoru
Abstract: Background: Fractional flow reserve (FFR) is useful for assessing the functional significance of coronary artery stenosis, even in lesions with prior myocardial infarction (pMI). Instantaneous wave-free ratio (iFR) is a vasodilator-free alternative for the physiological assessment of coronary artery stenosis. In addition, iFR shows good diagnostic agreement with FFR and an iFR-guided revascularization strategy was non-inferior to an FFR-guided revascularization strategy. However, the clinical usefulness of iFR for the evaluation of a coronary artery lesions with pMI has not been evaluated. Methods and Results: A total of 200 lesions from 200 patients (44 pMI territories lesions and 156 non-pMI coronary artery lesions) were analyzed retrospectively. Major adverse cardiac events (MACE) were defined as cardiovascular death, non-fatal MI, unstable angina pectoris, fatal arrhythmia and heart failure during 12 months follow-up after the physiological assessment of coronary artery stenosis. iFR was closely correlated with FFR in pMI and non-pMI lesions (r = 0.81 and 0.72; P < 0.001, respectively). In pMI lesions, an iFR cut-off of 0.89 was optimal against a clinical FFR cut-off of 0.80 according to receiver operating characteristics (ROC) curve analysis, whereas in non-pMI lesions, the iFR cut-off value was 0.92 without statistical significance. In addition, the event rate of MACE was similar between pMI and non-pMI patients during follow-up even in the presence or absence of an PCI procedure. Conclusions: iFR may be a useful alternative method compared with FFR for clinical decision-making even in pMI patients.